The role of religious brand community support to increase value co-creation in market religio-centric - Sudarti, Ken; Hendar, Hendar; Tharrazana, Nabila (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
This study analyzes the effect of religious brand community support (RBCS) in strengthening customer ethical perceptions (CEP) to establish trust and readiness for religious value co-creation. 212 Islamic clothing brand community members were the respondents in this study. They are involved in the purchasing interaction through online media, both consumer to consumer and consumer to the online shop owner. SEM was used to analyze and examine the empirical model. This study found that the role of RBCS in forming ethical perceptions regarding online shops can provide a sense of security, keep promises, and provide good service recovery. All of these impacts strengthen trust both with brands and online shop owners. Strengthening ethical perceptions and trust will increase consumer interest in the interaction of knowledge, experience, and religious belief that online shops can sell clothing products that are in accordance with religious law. The results of this study are beneficial for online shops that offer religious products, especially Islamic clothing, to manage a religio-centric market and strengthen a virtual community based on religious beliefs that are the same as the product value. This will strengthen the virtual halal ecosystem and provide a virtual da’wah space for religio-centric consumers who base all their activities on worship according to their religious values.